Establishment and characterization of biofloc culture for marbled crayfish - Coutinho Carneiro, Vitor; Schäfer, Ines; Diaz-Larrosa, J. Jaime; Böhl, Elias; Hahn, Thomas; Hempelmann, Jule; Venkatesh, Geetha; Nagarajan, Sanjanaa; Roy, Suki; Ng, Yi Long; Böhl, Florian; Zibek, Susanne; et al. (Frontiers in Aquaculture, 2025)
Biofloc technology is an innovative aquaculture approach that enhances water quality and reduces waste through the development of beneficial microbial communities. Marbled crayfish (Procambarus virginalis) are a newly discovered freshwater crayfish species that are distinguished by asexual reproduction, a genetically homogeneous all-female population structure and considerable robustness. These traits are attractive features for closed-system aquaculture production, which also mitigates the invasive risk associated with the species. Here we describe the establishment and characterization of biofloc culture for marbled crayfish. Juvenile crayfish raised in biofloc systems displayed robust growth with a six-fold weight increase over three months, comparable with other crustaceans under similar conditions. Metagenomic analysis revealed that biofloc communities consisted mostly of beneficial Gammaproteobacteria and Bacillariophyceae, with variations by environmental factors, such as temperature and light exposure. DNA methylation profiling identified systematic changes in response to biofloc environments, highlighting the potential of DNA methylation analysis for environmental biomarker identification. Finally, nutritional analysis showed that biofloc-grown crayfish produced meat with a highly favorable protein-to-fat ratio, while their shells retained considerable amounts of chitin, an important raw material for bioplastics production. Taken together, our study is the first to establish marbled crayfish biofloc culture and to characterize the interaction between the animals and the production system.